Lean Supply Chain Practices and Strangle Partnership with 3PLs for Supply Chain Performance: A Focal Firm Perspective - Tharaka, V.K.; Suraweera, R.N.; Galahitiyawe, N.W.K. (University of Sri Jayewardenepura, Nugegoda, 2017)
Supply chain performance have been discussed under efficiency and responsiveness measure in which this study argues that these two constructs are interrelated but opposing elements (duality). However, Qrunfleh and Tarafdar (2013) have empirically proven that the relationship between lean supply chain strategy and SC responsiveness is mediated by strategic partnership when the supply chain activities are outsourced. This study argues that the impact of ‘Lean’ practices are predominantly efficiency focused and hence Qrunfleh and Tarafdat (2013) study has to reconceptualised as supply chain performance rather than responsiveness. Thus, the primary purpose of this research is to uncover how lean supply chain strategies drive supply chain performance when the supply chain activities arc managed by outsourced parties. This study analysed 106 usable responses from 300 of population. The unit of analysis is manufacturing organizations in Sri Lanka who have outsourced at least one of their logistic activities to 3PL(s) and respondents were middle level managers. The data were analysed with Smart PLS. The finding indicates that, strategic partnership partially mediates the relationship between lean supply chain practices to SC performance. It further reveals that a stronger strategic partnership results in a higher performance than the direct Impact resulting from the lean practices. Thus, strategic partnership has become a requirement for not only responsiveness but also for efficiency. This study suggests that the collaborative planning, and trustworthiness as the most important considerations in a strategic partnership which leads to a beneficial partnership.
Keywords: Lean Supply Chain practices; Supply Chain Performance; Strategic Partnership; 3PLs